Ethnic entrepreneurs and movements for new administrative units: lessons from Nigeria - Saylor, Ryan (2016)
Many countries, especially in Africa, have increased their subnational administrative units in recent years. Researchers point to marginalized ethnic groups as a key force behind administrative subdivision. This article seeks to disentangle the relative influence of elites and the masses in prompting two movements for new administrative units in Nigeria (for Bayelsa and Ekiti states). I find that elites generated the movements, but not simply by mobilizing co-ethnics around an enduring identity. Rather, political entrepreneurs reconfigured ethnic boundaries and infused latent identities with new significance. They found ethnic appeals to be expedient for political mobilization. This finding cautions against interpreting ethnic mobilization for new districts as cultural groundswells. Overall, this article contributes to the emerging debate over the sources of demand for new administrative units in the developing world. - Reproduced.
Keywords: Ethnic groups; Public administration